Through a Community Economic Development Approach: A Comparative Study Between Cikedung Village and Anyar Village, Serang Regency, Banten Province - Nadiyah, Farkhanatun; Pradhani, Shavira Rizky; Alrasyid, Muhammad Alfin; Solihati, Keisha Dinya (KnE Social Sciences, 2025)
BUMDes refers to business entities that are wholly or partially owned by the village through direct participation to manage assets, services, and other businesses for the welfare of the community. The business owned by Anyar Village is bottled drinking water sourced directly from springs in the village, while Cikedung Village does not yet have a business and their BUMDes is still inactive. The purpose of this research is to determine the role of BUMDes in increasing the income and welfare of rural communities in Anyar and Cikedung villages. Using a qualitative research method, researchers conducted interviews and direct observation in both villages using a community economic development program approach. They concluded that BUMDes in Anyar village has played a role and contributed to village income and the welfare of the village community. Later, the success strategy of the Anyar Village’s BUMDes can be applied to the Cikedung Village’s BUMDes so that they can run actively and sustainably.